Reorganización del Sistema Contable en la Distribuidora Colchonbank de la Ciudad de Loja, Período Abril - Junio 2016 - Aguirre Rojas., Catalina Paola (2018)
The present thesis work entitled "Reorganization of the Accounting System in the Distribution Company" Colchonbank "of the City of Loja, period April - June 2016", is in its phase of economic growth, reason why it was necessary to have an adequate accounting organization that facilitates the control and registration of each and every one of its operations efficiently and in turn obtain real and reliable economic and financial information for a correct and accurate decision making. This thesis work was developed in compliance with the objectives, starting with the design of a plan and manual of accounts coded and ordered according to business requirements, which allowed to organize and record the daily operations of the Distributor; In order to continue with the development of the accounting process, the initial inventory was made, through the collection of the physical stock of merchandise and documents that support the rights and obligations of the company, then proceeded to prepare the Initial Situation Statement and the memorandum of operations allowing this way to make the daily book and control of the merchandise account through sales and purchasing assistants until its regulation or adjustment corresponding to the end of the accounting period, in addition to the majority of each and every one of the resulting accounts of the daily book, for later verification of balances in the trial balance and worksheet where the adjustments were made corresponding, and finally the financial statements were elaborated, through them the economic and financial 5 performance of the company was analyzed to facilitate decision making. At the end of the accounting reorganization process, the financial statements were presented and analyzed, through Financial Analysis and Indicators to evaluate the Company's Financial and Economic performance, obtaining as results that the Distributor has a positive value to cover its obligations with third parties, not having any risk of inability to pay. In addition, it became necessary to use methods, procedures and research techniques that helped the collection and processing of information related to the requirements of the subject of study. The most important conclusion reached after completing this thesis is that the Colchonbank Distributor did not have an accounting organization that provides accurate and timely financial and financial information on the daily operations it carries out, for which recommends the proposed accounting reorganization in order to know its current financial economic situation, through the financial statements and Financial Indicators.